Mapping the Role of Electrochemistry in Advancing Sustainable Development through Chemistry Education - Fitri, Hajidah Salsabila Allissa; Ma'arif, Alfian; Rashid, Salman; Kalyazifa, Davira Oxana; Joronavalona, Rasamimanana (Control Systems and Optimization Letters, 2026)
The integration of electrochemistry and sustainable development has gained increasing scholarly attention in response to global energy transitions and sustainability agendas. This study maps the evolution, intellectual structure, and emerging themes of research at the intersection of electrochemistry, sustainable development, and chemistry education using a bibliometric approach. A total of 2,204 publications indexed in Scopus between 2000 and 2026 (with 2026 data limited to publications available up to February) were analyzed using Biblioshiny and VOSviewer. The results show a sharp increase in publication output after 2018, reflecting growing interest in sustainability-oriented electrochemical research. Research productivity and citation impact are concentrated in countries such as China and the United States, as indicated by publication counts and citation metrics. Thematic analyses reveal that dominant research areas are driven by technological domains, particularly lithium ion batteries, hydrogen production, electrocatalysis, and machine learning applications. Overlay and trend analyses further indicate the recent expansion of data-driven approaches in electrochemical research. However, only a limited proportion of publications explicitly address educational perspectives, indicating that pedagogical constructs remain peripheral within the field. In this study, transformative educational perspectives refer to approaches that integrate sustainability competencies, systems thinking, and real world problem solving into chemistry learning. The findings suggest a growing imbalance between rapid technological advancement and relatively limited pedagogical integration. This study provides a structured overview of research development and highlights the need for stronger alignment between electrochemical innovation and sustainability-oriented chemistry education.